Synthesis of Silver and Carbon Nanoparticles in Surface Plasmon Resonance and Electrochemical Biosensors for Japanese Encephalitis Virus (JEV) Detection - Lim, Lih Shan (Universiti malaysia sarawak (UNIMAS), 2017)
Nanoparticles are widely use in biosensing application due to their high surface areas to volume ratio property, can provide high loading of biomolecules onto biosensor surfaces. In this research, Ag NPs and CNPs were utilized for JEV biosensing purposes. Ag NPs-based SPR sensing probe was developed by the deposition of Ag NPs onto glass slides. The detection of JEV was observed via changes in light absorbance by Ag NPs on glass slides upon an occurrence of JEV-antibody binding. This sensing probe had LOD of 12.8 ng/mL of JEV and an analysis assay time of 1 h. Besides, Ag NPs were employed and developed into electrochemical biosensor. Ag NPs-modified SPCE was fabricated by deposition of Ag NPs onto SPCE working electrode surface and successfully increased the current intensity up to 19.04 % than that of bare SPCE. Under optimized parameters, the detection range was 10 to 30 ng/mL, with LOD of 3.88 ng/mL of JEV, and a response time of 20 min. The performance of Ag NPs-modified SPCE was found to be superior to Ag NPs-based sensing probe in term of LOD, fabrication procedure and analysis assay time of JEV. As for CNPs-modified SPCE, CNPs were deposited onto 3-aminopropyl triethoxysilane (APTES) functionalized SPCE working electrode surface, followed by immobilization of JEV antibody onto CNPs surfaces. It was observed that the deposition of CNPs had enhanced the current intensity of the SPCE up to 63 % as compared to bare SPCE. Under optimized conditions, this biosensor demonstrated a linear response range to target JEV (5 to 20.0 ng/mL) with LOD of2.0 ng/mL and an analysis assay time of20 min.